2018
DOI: 10.1101/451963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anteroposterior patterning of the zebrafish ear through Fgf- and Hh-dependent regulation ofhmx3aexpression

Abstract: 23In the zebrafish, Fgf and Hh signalling assign anterior and posterior identity, 24 respectively, to the poles of the developing ear. Mis-expression of fgf3 or inhibition of 25Hh signalling results in double-anterior ears, including ectopic expression of hmx3a. 26To understand how this double-anterior pattern is established, we characterised 27 transcriptional responses in Fgf gain-of-signalling or Hh loss-of-signalling 28 backgrounds. Mis-expression of fgf3 resulted in rapid expansion of anterior otic 29

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 53 publications
4
6
1
Order By: Relevance
“…Consistent with previous reports, both of these genes are also expressed in the lateral line and developing ear (Fig. 1;Adamska et al, 2000;Feng and Xu, 2010;Hartwell et al, 2019) as well as distinct regions of the brain (data not shown).…”
Section: Introductionsupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with previous reports, both of these genes are also expressed in the lateral line and developing ear (Fig. 1;Adamska et al, 2000;Feng and Xu, 2010;Hartwell et al, 2019) as well as distinct regions of the brain (data not shown).…”
Section: Introductionsupporting
confidence: 93%
“…Previous research has shown that Hmx2 and Hmx3 have crucial functions in ear development in mouse and our recent work shows that this is also the case for Hmx3a in zebrafish (Hartwell et al, 2019;Wang et al, 2001;Wang et al, 2004;Wang and Lufkin, 2005;Wang et al, 1998; see also Feng and Xu, 2010). These genes are also required for correct specification of the mouse hypothalmus (Wang et al, 2004) and morpholino knock-down experiments have suggested that they are required for correct progression of the lateral line in zebrafish (Feng and Xu, 2010).…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations